Virus disease in wheat predicted to increase with a changing climate. (8th June 2015) - Trębicki, Piotr; Nancarrow, Narelle; Cole, Ellen; Bosque‐Pérez, Nilsa A.; Constable, Fiona E.; Freeman, Angela J.; Rodoni, Brendan; Yen, Alan L.; Luck, Jo E.; Fitzgerald, Glenn J.
Abstract Current atmospheric CO2 levels are about 400 μmol mol−1 and are predicted to rise to 650 μmol mol−1 later this century. Although the positive and negative impacts of CO2 on plants are well documented, little is known about interactions with pests and diseases. If disease severity increases under future environmental conditions, then it becomes imperative to understand the impacts of pathogens on crop production in order to minimize crop losses and maximize food production. Barley yellow dwarf virus (BYDV) adversely affects the yield and quality of economically important crops including wheat, barley and oats. It is transmitted by numerous aphid species and causes a serious disease of cereal crops worldwide. This study examined the effects of ambient (aCO2; 400 μmol mol−1) and elevated CO2 (eCO2; 650 μmol mol−1) on noninfected and BYDV‐infected wheat. Using a RT‐qPCR technique, we measured virus titre from aCO2 and eCO2 treatments. BYDV titre increased significantly by 36.8% in leaves of wheat grown under eCO2 conditions compared to aCO2. Plant growth parameters including height, tiller number, leaf area and biomass were generally higher in plants exposed to higher CO2 levels but increased growth did not explain the increase in BYDV titre in these plants. High virus titre in plants has been shown to have a significant negative effect on plant yield and causes earlier and more pronounced symptom expression increasing the probability of virus spread by insects. The combination of these factors could negatively impact food production in Australia and worldwide under future climate conditions. This is the first quantitative evidence that BYDV titre increases in plants grown under elevated CO2 levels.